Remittance and Dutch Disease Phenomenon: Case of Bangladesh and Pakistan - Sultana, Sharmin (Asian Business Review, 2021)
The paper has been designed to explore whether the impact of remittance on the real exchange rate causes any Dutch disease problem for Bangladesh and Pakistan. These two South Asian countries have been targeted to figure out if the outcomes are similar for the countries with almost the same economic structure. Johansen co-integration approach, Vector Error Correction Method (VECM), and Granger Causality test have been employed taking real exchange rate as regressand and remittance and other attributing variables as explanatory variables with an aim to address the study objective. The study has used data from the World Development Indicators database ranging from 1986 to 2019. The results for both countries reveal that remittance is significantly negatively related to the real exchange rate which implying the appreciation of the domestic currency. However, this appreciation causes the Dutch disease phenomenon for neither Bangladesh nor Pakistan.